A contribution to Czechoslovak-Yugoslav economic relations in the 1920s - Jakab, František (Napredak, 2026)
The study focuses on Czechoslovak-Yugoslav economic relations during the 1920s. Its aim is to analyze the reasons for their problematic development, which never fulfilled their potential enabled by the differing nature of the economies, close political ties, and membership in the Little Entente. The results, based on a review of secondary literature and archival research in Prague and Belgrade, identify the main causes of this failure as the character of Czechoslovak economic policy, its expansionist nature, and the rejection of Yugoslav imports. Furthermore, bilateral complications in negotiations on trade agreements, the introduction of import duties, and numerous disputes typical of Czechoslovak-Yugoslav trade cannot be overlooked. Economic relations that could have strengthened bilateral ties ultimately became their weakness.
Keywords: Czechoslovakia; Yugoslavia; economic relations; Little Entente; interwar period